Investigation of the copolymerization of butyl acrylate (BA) with vinyl neononanoate (VeoVA-9) - Hadasha, Waled (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2006.